Novel Tricyclic Flavonoids as Promising Anti-MRSA Agents - Cristina-Veronica Moldovan; Loredana-Elena Mantea; Mihaela Savu; Peter G. Jones; Laura Gabriela Sarbu; Marius Stefan; Mihail Lucian Birsa (MDPI AG, 2024)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is considered the main cause of nosocomial and community-associated infections. Because of antimicrobial resistance, MRSA infections are difficult or impossible to treat, leading to high mortality rates and significant economic and societal costs. In view of the MRSA challenge to public health all over the world, the identification of new and effective anti-MRSA agents is a high medical priority. Objectives: A new series of tricyclic flavonoids with a methyl substituent on ring A of the flavonoid skeleton was synthesized to assess their antimicrobial properties. Methods: The structures of novel synthetic tricyclic flavonoids and their 3-dithiocarbamic flavanones were proven by X-ray structural analyses. Minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC) were used to evaluate antimicrobial activity. Growth kinetic and time-kill assays were employed to confirm the antibacterial effectiveness. The mechanism of action was investigated using fluorescence microscopy. Results: Our results show that the tricyclic flavonoids exhibited important antibacterial and antifungal activities, with MIC and MBC values as low as 1.95 µg/mL and 3.90 µg/mL recorded for compound 5e against a multidrug-resistant MRSA strain. Flavonoid 5e induced a more important bacteriostatic effect compared with chloramphenicol, inhibiting the bacterial growth for up to 24 h at concentrations equivalent to 2 × MIC. Also, 5e exhibited a significant bactericidal activity, with no viable cells evidenced after 6 h of incubation in the presence of MBC and a total kill effect recorded up to 24 h. The anti-MRSA activity may be explained by the cell membrane impairment induced by 5e. Conclusions: All the data support the idea that flavonoid 5e is a reliable candidate to develop effective anti-MRSA agents, but further studies are necessary.